FORMULATION OF VITAMIN COMPLEXES, SUPPLYING PHYSIOLOGICAL NEEDS IN VITAMINS IN CHILDREN - O.A. Gromova (Вопросы современной педиатрии, 2009)
Technological progress saved human from hard physical work and big expenditures of energy. It was resulted in need to decrease the volume of consumed food. But need in vitamins remained on the former level. Maximal volume of vitamins, which organism use, is conditioned on the level of genes. The reasons, allowing a development of state of hypovitaminosis especially in schoolchildren, remain. Increased metabolism, induced by the growth of organism, frequently inevitable stress, sometimes unbalanced nutrition, hard intellectual loads, etc., can lead to the development of the states, which need increased doses of vitamins. Observations during last 20 years showed that there is no almost any child, whose provision with vitamins con be estimated as optimal. In most children (up to 70%) the combined deficiency of three and more vitamins is detected, independently of their age, time of year and place of living. Pediatricians use vitamins not only for the maintenance of homeostasis itself, but for the initiation of all program of child’s development. Schoolchild’s organism needs additional volume of vitamins all the time, and they should be administrated during prolonged periods of time, independently of time of the year and adequacy of diet. Timely administration of vitamins and minerals complexes provides significant prophylactic of hypovitaminosis.Key words: children, vitamins, nutrition, prophylaxis.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2009;8(6):77-84)